Approaches to Household Inventories and Household Furnishing, 1500–1650. Issue 1 (November 2015) - Pearce, Michael
Abstract : Inventory texts are structured and patterned by social priorities as interesting as the artefacts described. Reconstructing those priorities leads to a better understanding of the significance of furnishing within architectural planning. This article presents the hall as central to the demonstration of inequality of wealth and power within sixteenth- and seventeenth-century elite domestic architecture and, using inventories which have not been closely examined before, identifies and explains the role of the key furnishings.